Nghiên cứu xung đột trong kịch Lưu Quang Vũ - Vũ, Thị Thanh Hoài (Tạp chí thiết bị giáo dục, 2023)
Abstract: Drama is a general art form, often composed into works to be performed on stage or in cinema. For the drama genre, many teachers still consider it difficult to teach. Drama is written to act, so the object of the drama's description is the conflicts in daily life. To contribute to improving the effectiveness of Luu Quang Vu's drama teaching, the author analyzes conflicts in Lui Quang Vu's plays.